2016
DOI: 10.1530/joe-16-0332
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide and pasireotide (dis)similarly inhibit pituitary tumor cells in vitro

Abstract: Somatostatin analogs (SSA) are the mainstay of pharmacological treatment for pituitary adenomas. However, some patients escape from therapy with octreotide, a somatostatin receptor 2 (sst2)-preferring SSA, and pasireotide, a novel multi-sst-preferring SSA, may help to overcome this problem. It has been proposed that correspondence between sst1-sst5 expression pattern and SSA-binding profile could predict patient's response. To explore the cellular/molecular features associated with octreotide/pasireotide respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 41 publications
(65 reference statements)
8
78
0
1
Order By: Relevance
“…Analogous findings of decreased cell viability have been shown with the use of octreotide and pasireotide in various types of pituitary tumors, regardless of SSTR subtype expression pattern, in vitro 39. The findings of the present study suggest this may be mediated by SSTR-induced upregulation of the direct pro-apoptotic factor BAX.…”
Section: Discussionsupporting
confidence: 85%
“…Analogous findings of decreased cell viability have been shown with the use of octreotide and pasireotide in various types of pituitary tumors, regardless of SSTR subtype expression pattern, in vitro 39. The findings of the present study suggest this may be mediated by SSTR-induced upregulation of the direct pro-apoptotic factor BAX.…”
Section: Discussionsupporting
confidence: 85%
“…No patient received radiotherapy before surgery. Of the 74 patients, we were able to obtain reliable biochemical data to evaluate response to SSAs treatment from 58 patients either before surgery (30) or adjuvant (28). Missing data were due to incomplete follow-up.…”
Section: Patients and Samplesmentioning
confidence: 99%
“…Some components of this system have been previously associated with development and progression of tumoral pathologies, such as pituitary adenomas, thyroid cancer, neuroendocrine tumors (NETs), and breast cancer, where they may exert an important role as diagnosis/prognosis markers and therapeutic targets . In fact, somatostatin analogs (eg, the sst2‐preferring octreotide and lanreotide, and the pan‐sst ligand pasireotide) are currently being used to treat some of these pathologies, such as pituitary adenomas and NETs, highlighting the clinical relevance of this system …”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] In fact, somatostatin analogs (eg, the sst2-preferring octreotide and lanreotide, and the pan-sst ligand pasireotide) are currently being used to treat some of these pathologies, such as pituitary adenomas and NETs, highlighting the clinical relevance of this system. [25][26][27] It has been demonstrated that the expression of some components of the SST system, especially sst variants, are dysregulated in PCa tissue and associated with the aggressiveness of tumor cells, [28][29][30] which highlights the putative utility of these components as novel biomarkers and therapeutic targets to develop pharmacologic strategies for this pathology. In this sense, SST receptor subtype 1 (sst1, SSTR1) has been described as an important molecule in several types of cancer, such as colon cancer, where it seems to play a significant role and is associated with some aggressiveness features.…”
Section: Introductionmentioning
confidence: 99%